Techniques and technologies journalist training (Herald of Journalism, 2021)
Modern approaches to the training of media specialists are undergoing significant changes, as evi- denced by scientific forums of journalists (researchers and practitioners) with the inclusion of sociolo- gists, philosophers, political scientists, PR managers in the dialogue; representatives of different branches of the media space (financial, legal journalism). After the introduction of the course «Multimedia Journal- ism» into the curriculum of secondary schools, the voices of teachers are «heard».During the creative examination for admission to the Faculty of Journalism, for the applicant the main criterion for choosing the specialty «Journalism»: «I want to become a journalist: I love and know how to communicate.» However, after admission and study, there are often cases of disappointment. It is important for the teacher to establish the reasons for the decline in interest in the profession, to minimize risks and improve the quality of teaching. Recall that a professional journalist in the regional media is assigned a much greater measure of social responsibility. Journalist represents the «fourth estate» in the country, defending the interests of the people and the democratic principles of society. The purpose of our research within the framework of the article is to identify relevant and interactive learning models in journalism based on the experience of diagnosing thinking, technical, technological skills and student motivation.For a number of years, a student, studying at the Faculty of Journalism, asks himself the following questions: is it necessary to study journalism; is this profession so interesting and prestigious; Is there high competition among specialists? The authors analyzed various modern trends of a successful media personality and, finally, came to the conclusion that this category of students did not have the skill to write texts correctly.In the course of our research, we have identified four levels of conditional «identification» of a future media specialist: 1) applicant «no-name»; 2) freshman hesitant; 3) a doubting senior student; 4) the graduate is «in trend». In the course of observation, we have established: already from the middle of the second year, the specialty – journalism is not considered by students as a profession for life. Accordingly, at each stage, we have determined: the focus of observation, developed educational content and behavioral model.Working hypothesis: if at each stage «lay a creative» component, which, with basic skills and a new educational policy, guarantees a competitive specialist by the end of the faculty. The result of the study can be considered a study of the model of the formation of journalists in the system: university-creativity- practice, based on multimedia and the principles of effective communication.Key words: methodology; integrative technologies; professional practices; strategy; the media sphere.